Exploratory Study on Inclusion in the Workplaces in Malang - Widyarini, Ika; Widyasari, Selly Dian (The Center for Disability Studies and Services Brawijaya University, 2023)
This study aims to determine the antecedents, aspects and implications of implementing inclusion, especially the inclusion of persons with physical and mental disabilities in workplaces in the Malang area. This is a qualitative research, data collection was carried out through a systematic literature review of the study database on inclusion in the workplace and will be supported by in-depth interviews and leaderless group discussions (LGD) to collect data from government sources such as Malang Manpower Offices, and organizations or institutions in the Malang area that enforce inclusion of persons with disabilities as the main stakeholders. The data obtained will be analysed using reduction techniques and presented in the form of a proposal for an integrated inclusion implementation model. This research is to provide an overview of the implementation of inclusion at the organizational level. This conceptual model will be the basis for creating measurement of the inclusion level in the workplaces in Indonesia. From this conceptual understanding and preparation of measurements, it is hoped that we can measure how successful an implementation of inclusion in a work environment.